Selection of reliable reference genes in Colletotrichum scovillei during different growth stages, host interactions, and plant extract treatment for qRT-PCR - Guo Geng Jia; Sun Ha Kim; Jiyoung Min; Nelson Villalobos Zamora; Silvia Soto Montero; Dong-Keun Yi; Soo-Yong Kim; Sang-Keun Oh (BMC Plant Biology)
Abstract Selection of a reliable internal control gene is critical for quantitative real-time PCR, which is a rapid, highly sensitive, and easy method for evaluating gene expression levels in different samples or tissues. Colletotrichum scovillei, which belongs to the C. acutatum species complex, is a common and aggressive species that can cause anthracnose in chili peppers. However, stable reference genes have not yet been identified for C. scovillei. In our study, reference genes were selected and validated in C. scovillei during different growth stages, including conidia, conidial germination, and mycelium growth, during host interactions, and after treatment with the common solvent 0.5% dimethyl sulfoxide (DMSO) and plant extracts with antifungal activity against C. scovillei. Eight candidate reference genes (CsUCE, CsCK, CsTBP, CsTIF, CsPP2A, CsTUB, CsCAL, and CsNADH) were selected from C. scovillei based on transcriptomic and genomic data. Several statistical methods, including the comparative quantification cycle threshold (Ct) method, geNorm, NormFinder, and Bestkeeper, were used to assess the stabilities of reference gene transcripts. The results indicated that CsPP2A had better stability during the C. scovillei growth stage, CsTUB had the best stability during host interactions, and CsUCE was more stable after treatment with the general solvent 0.5% DMSO and Cestrum glanduliferum kerber ex Francey extracts. Our study provides the most suitable reference gene for future studies to quantify target gene expression levels in C. scovillei under different conditions.